Evaluation of diagnostic accuracy of latex agglutination test and E-test for the detection of methicillin-resistant Staphylococcus aureus - Gupta, Nupur; Jais, Manoj; Sharma, Aditi; Shrivastava, Priyanshu K. (International Journal of Scientific Reports, 2023)
Background: This study was undertaken to compare the phenotypic methods of latex agglutination test and e-test with polymerase chain reaction for the detection of methicillin-resistant Staphylococcus aureus. Methods: Two hundred pus samples obtained from different clinical disciplines were subjected to the latex agglutination test and minimum inhibitory concentration by e-test (Oxacillin and Vancomycin) as per the standard guidelines. The comparison was made with polymerase chain reaction as the reference test. The diagnostic accuracy of each method was reported in terms of sensitivity, specificity, positive predictive value, and negative predictive value. Results: The sensitivity of latex agglutination test was found to be 100% whereas e-test for Oxacillin was found to be 96.67% sensitive. Higher specificity for e-test was reported (99.41%) when compared to the latex agglutination test (97.65%). Conclusions: Latex agglutination and e-tests are tests are relatively simpler, rapid, and easy-to-perform methods when compared to polymerase chain reaction. The present study reported high sensitivity and specificity values for both the tests, and therefore supports usage of the stated methods as screening tools for methicillin-resistant S. aureus. However, more multi-centric studies are recommended to precisely determine the diagnostic accuracy of these phenotypic methods.